THE IMPACT OF INQUIRY-BASED LEARNING ON LEARNERS' UNDERSTANDING OF CHEMICAL CHANGE: A QUASI-EXPERIMENTAL STUDY - Nkosi , Nkosinathi Willy; Motlhabane, Abraham Tlhalefang (UNESA Journal of Chemical Education, 2025)
Chemical change is a fundamental yet challenging concept in Chemistry. This quasi-experimental study used a pretest-posttest non-equivalent groups design to investigate the impact of inquiry-based learning on learners' conceptual understanding of chemical change. Seventy-three learners received inquiry-based instruction, while sixty-nine learners received traditional teaching methods. The results showed significant improvement in the experimental group's conceptual understanding, with medium to high N-Gain scores indicating notable enhancement.  In contrast, the control group demonstrated minimal improvements, with low N-Gain scores indicating limited enhancement. The findings suggest that inquiry-based learning effectively promotes learners' conceptual understanding of chemical change. This approach encourages active engagement with scientific concepts, develops critical thinking skills, and fosters a deeper understanding of complex phenomena. The study's results have implications for science education, highlighting the importance of incorporating inquiry-based learning into the science curriculum. The findings contribute to existing research on inquiry-based learning, underscoring its potential to enhance learners' conceptual understanding and promote excellence in science education.